Penyuluhan Jajanan Sehat pada Anak Usia Dini di Paud Al-Mubtadi Desa Padang Tikar Kabupaten Kubu Raya - Indah Istikhomah; Dwi Khalisa Putri (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
This community service activity is motivated by the presence of unhealthy food or snacks being sold in the school canteen and the surrounding area. Based on initial observations, this was also found in several schools located in Padang Tikar 1 Village, specifically in Kubu Raya Regency. Some examples of snacks provided at the canteen are: noodles, skewered meatballs, skewered sausages, fried snacks, and packaged snacks. PKM will be conducted on February 29, 2024. Objective: To enhance the knowledge of young children about consuming healthy food. Method: The service was carried out at AlMubtadi Kindergarten, attended by children and parents. The service team conducted a pretest before the implementation of the counseling on healthy snacks, presented through PowerPoint. Subsequently, after the PowerPoint presentation, the service team administered a posttest to be filled out by the parents. The results based on the pre-test and post-test data indicate an increase in knowledge among kindergarten children about healthy snacks. Out of 30 respondents, before the counseling was provided, 11 individuals, or 36.7%, had limited knowledge. After the counseling, this improved to 20 individuals, or 66.7%, demonstrating good knowledge. In conclusion, counseling on healthy snacks can enhance knowledge and train both children and parents in selecting snacks sold in the school environment.